A Policy Perspective on Tobacco Farming and Public Health in Indonesia - Pingkan Audrine (Center for Indonesian Policy Studies (CIPS), 2020)
Indonesia's cigarette industry is a significant contributor to employment and tax revenue collection. However, it is also responsible for enormous public health and economic costs, as smoking related health expenditures in Indonesia amount to approximately USD 1.2 billion per year and another USD 6.8 billion in indirect economic costs. Hence, policies targeting the tobacco farming and cigarette industries face a dilemma of public health versus rural livelihoods. This policy paper outlines policy ideas and recommendations for Indonesian policymakers with the aim of reducing cigarette consumption in Indonesia. The paper also explores the need for technical support to enable farmers to grow tobacco for other purposes besides traditional cigarettes.
Keywords: 330; tobacco; cigarette; farmers; smoking; ends; vape; electric cigarette; health policy; tobacco farming; tax revenue; cigarette industri